Gastrointestinal helminth of Nile crocodiles (Crocodylus niloticus), in Arba Minch Crocodile Ranch, Ethiopia - Meheret Utele; Alemayehu Gebeyehu; Tamirat Kaba (Scientific Reports)
Abstract Parasites are among the major organisms that affect the health of crocodiles. A cross-sectional study was conducted from November 2021 to May 2022 aimed to determine the prevalence of gastrointestinal helminths of Nile crocodiles in Arba Minch Crocodile Ranch (AMCR), Ethiopia. A total of 322 fecal samples were collected using a random sampling technique. Standard parasitological tests were used to identify the gastrointestinal helminth parasite. Out of 322 fecal samples examined, 102(31.68%) were found positive for gastrointestinal helminths. Among the endoparasite eggs detected Dujardinascaris (18.01%) species was the most dominant species followed by Trichinella species (5.62%), polydeliphs (3.1%) and Renifers species (0.62%). There was a statistically significant difference(P = 0.0001) in the prevalence of helminth parasites between male (15.97%) and female (44.38%) crocodiles. Likewise, the prevalence of helminths between different age groups was determined with the highest prevalence in crocodiles of less than 8 years old (41.9%) and the lowest prevalence in crocodiles of age greater than 11 years (19.56%). It has been observed that the crocodile in the area of study had mixed infestation with more than one parasite. The study revealed that gastrointestinal parasites were prevalent in the ranch. Therefore, strict prophylaxis treatment and hygiene should be performed in the study area.